Supporting the Inclusion and Identities of African Refugee Students in U.S. Higher Education - Habtemariam, Samuel (Issues in Language Instruction, 2025)
This paper seeks to understand how African refugee students in U.S. higher education construct their social and schooling identities while they negotiate the challenges they face. Although existing literature address- es identity formation among refugee students in the post resettlement period, little is known about how African adult college refugee students maintain their identities once settled in the United States. Framed as a qualitative case study, findings assert that African refugee college students face both linguistic and academic challenges as students enrolled in higher education in the U.S.; however, the magnitude of the linguistic challenges varies based on the status of English language as a medium of instruction in the country of the refugees’ first asylum. The two challenges—linguistic and academic challenge—become intertwined once refugees pursue post-secondary opportunities in the U.S. Findings highlight the juxtaposition of maintenance of previous schooling and cultural values while learning and negotiating a new culture of post-secondary schooling in the U.S.